ANALISIS OF QUALITY MANAGEMENT HEALTH CARE INPATIENT ON GENERAL HOSPITAL PANGKEP IN 2014 - Herman (Jurnal Mitrasehat, 2018)
The main purpose and this study are to the satisfaction of patients in terms of punctuality, The satisfaction of patient in terms of information, the satisfaction of patients in terms of technical competence, the satisfaction of patients in terms of human relations, The satisfaction of patients in terms of convenience, the objective of the study was to understand and analyze resident satisfaction with health quality at the local government general hospital of Pangkep Regency. The method of this study is to analyze facts regarding the view from punctuality, information, technical competence, human relation, and convenience on patient satisfaction with the service experience at the local government pangkep Regency. The data for the study was collected through questionnaires and observation. The population of the study was all patients and their family members residing in the pavilion room. The results of the study showed patient satisfaction with a quality experience at the local Government Pangkep was categorized as high. The patients were satisfied with the quality of their experience. The satisfaction of patients in terms of punctuality. The satisfaction of patients in terms of information, The satisfaction of patients in terms of human relations. The satisfaction of patients in terms of convenience. The satisfaction and quality certainty were also categorized based on the study result. It was suggested that the hospital management could always improve the doctors' and nurses' quality and increase the number of pavilion rooms.